A Comparison Between The 5:2 And 16:8 Intermittent Fasting Methods on Weight Loss in Overweight And Obese Individuals - Ayudia, Esa Indah; Calista, Amanda Athiyyah; Enis, Rina Nofri; Perkasa, Tengku Arief Buana; Anggraini, Bayu; Asyhar, Rayandra (Jambi Medical Journal : Jurnal Kedokteran dan Kesehatan, 2025)
ABSTRACT Background: Overweight and obesity are conditions characterized by excess body weight, which increase the risk of chronic diseases. One of the main contributing factors is dietary habits. A popular intervention for weight loss is the Intermittent Fasting (IF) diet, particularly the 5:2 and 16:8 methods. This study aims to compare the effectiveness of the 5:2 and 16:8 IF methods in reducing body weight among overweight and obese individuals. Methods: This research employed a pre and post test design involving 50 respondents, divided into two groups, and subjected to a 6-week intervention. Data were analyzed using the Paired Sample T-Test (for IF 5:2), the Wilcoxon Test (for IF 16:8), and the Mann-Whitney Test for comparison between the two groups. Results: The results showed that the IF 5:2 group experienced an average weight loss of 3.38% (p < 0.001), while the IF 16:8 group had a weight loss of 2.28% (p = 0.000). The comparison between the two groups yielded a p-value of 0.081. Conclusion: Both IF methods, 5:2 and 16:8, are effective in significantly reducing body weight. Although the 5:2 method resulted in a greater weight loss, the difference between the two methods was not statistically significant.